The Guanine-Based Purinergic System: The Tale of An Orphan Neuromodulation - Di Liberto, Valentina; Mudò, Giuseppa; Garozzo, Roberta; Frinchi, Monica; Fernandez-Dueñas, Víctor; Di Iorio, Patrizia; Ciccarelli, Renata; Caciagli, Francesco; Condorelli, Daniele F.; Ciruela, Francisco; Belluardo, Natale (Frontiers in Pharmacology, 2016)
Guanine-based purines (GBPs) have been recently proposed to be not only metabolic agents but also extracellular signaling molecules that regulate important functions in the central nervous system. In such way, GBPs-mediated neuroprotection, behavioral responses and neuronal plasticity have been broadly described in the literature. However, while a number of these functions (i.e GBPs neurothophic effects) have been well-established, the molecular mechanisms behind these GBP-dependent effects are still unknown. Furthermore, no plasma membrane receptors for GBPs have been described so far, thus GBPs are still considered orphan neuromodulators. Interestingly, an intricate and controversial functional interplay between GBPs effects and adenosine receptors activity has been recently described, thus triggering the hypothesis that GBPs mechanism of action might somehow involve adenosine receptors. Here, we review recent data describing the GBPs role in the brain. We focus on the involvement of GBPs regulating neuronal plasticity, and on the new hypothesis based on putative GBPs receptors. Overall, we expect to shed some light on the GBPs world since although these molecules might represent excellent candidates for certain neurological diseases management, the lack of putative GBP receptors precludes any high throughput screening intent for the search of effective GBP-based drugs.